The effects of horticultural farmer group performance on motivation, training, and production facilities - Hironimus Mawo Dopo; Philipus Tulle; Gaudensius Djuang (Institute of Computer Science (IOCS), 2023)
The objective of this research was to learn more about the West Miomaffo District, North Central Timor Regency's horticultural farmers' motivation, training, production capabilities, and performance. With a population of 4,160 and a sample of 94 respondents, this study falls within the quantitative research area. The descriptive analysis's findings demonstrate that farmers had positive perceptions of the factors of motivation, training, production capabilities, and farmer performance. While the results of the inferential analysis demonstrate a significant linear relationship between Horticultural Farmer Performance (Y) and the variables Motivation (X1), Training (X2), and Production Facilities (X3), the results of the t test demonstrate a positive correlation between each of these variables and Horticultural Farmer Performance (Y).